Analisis Ketimpangan Distribusi Pendapatan pada Kabupaten/Kota di Provinsi Bali - Mestor Lotam Apriadil Purba; Sudarsana Arka (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Economic development aims to improve the well-being of the population, as reflected in the increase of the Human Development Index (HDI). Although the HDI in the regencies/cities of Bali Province has risen, income disparity persists. Reducing income distribution inequality can be achieved by creating decent job opportunities, lowering unemployment rates, and providing adequate income to ensure a good quality of life for workers. The objectives of this study are (1) To analyse the simultaneous effect of unemployment, economic growth and human development index on income distribution inequality in regencies/cities in Bali Province. (2) To analyse the partial effect of unemployment, economic growth and human development index on income distribution inequality in regencies/municipalities in Bali Province. The data used is secondary data, with 117 observation points. The analysis technique used is panel data regression model technique. The results showed that (1) Unemployment, economic growth and human development index simultaneously affect the inequality of income distribution in regencies/cities in Bali Province. (2) Unemployment and economic growth have a positive effect but not significant on income distribution inequality, while the human development index has a negative and significant effect on income distribution inequality.